Auditoria operativa al departamento de bodega y su incidencia en la liquidez de la empresa agrícola bananera agripalban S.A. Ubicada en el cantón Valencia, primer semestre del año 2013 - Punin Ibarra, Iliana Katherine (2015)
This Thesis was held in the company AGRIPALBAN SA, located in the canton Valencia province of Los Rios. The research aimed to perform an operational audit department winery to determine their impact on the liquidity of the company. The research was conducted using a bibliography for fundament the audit process and field research for the collection of information. By the inductive method, statistical analysis was performed to obtain information results that support the conclusions. Applying an audit based on methodologies, standards and regulations were performed each phase, identifying business structure and management of the company through the study of the organization and its management through scheduled visits to the facility, to observe the development operations. After evaluating the level of compliance with the internal control of the company, it could determine the effectiveness of the operations of the audited area. Among the failures it was found that the application of inventory valuation methods are inappropriate and not stock estimation activities are carried out, making it impossible to project a proper supply to their internal customers. Like many companies, some of the rules and procedures are not clearly defined, although the accounting rules are generally observed. The evaluation of internal control for the administrative process, obtained a Risk Control 74% equivalent to a moderately high risk level and a confidence level of 26%, ie, Low. As for the evaluation of internal control for the operational management of Bodega area, it was found that the Risk Control 57% equivalent to a moderate level Low and a confidence level of 43%, ie, low. Loss items definitely affect the profitability of the company, reporting a total of $ 10,720.25 which is unexplained. The findings which were properly informed together with proposals for improvement of their operations.